Intestinal parasitic diseases in junior wrestlers: Imitation of overtraining syndrome - Kerimov, F. A.; Islamova, J. I.; Davis, N. A.; Syrov, V. N.; Ocipova, S. O. (International Journal of Wrestling Science, 2014)
Significant muscle loading in elite athletes result in considerable changes in their physiological and immune status. There can be variations in the concentrations of serum IgM, IgG and IgA - from significant decrease to elevation, reduction of total serum IgE, an increase in the level of proinflammatory cytokines, etc. (5, 13, 10). Therefore, health status monitoring is of great importance, especially in the diagnosis of diseases. The intense training of an athlete can cause a negative influence on the immune state, raise susceptibility to bacterial and viral infections, induce functional disorders of the hepatobiliary system. Intestinal parasitic diseases (IPD) induce such changes (4, 6). Their timely diagnosis and adequate therapy are of peculiar importance in regions endemic with IPD. Uzbekistan belongs to such a region (1).